The Coercion-Manipulation-Persuasion Framework: Analyzing the Modus Operandi of Systems of Non-State Actors - Alonso-Villota, Marina (Terrorism and political violence, 2025)
Non-state actors conducting terrorist attacks have shown to also rely on a mosaic of tactics to advance their strategic agendas, such as misusing educational curricula, infiltrating political institutions, and providing welfare, among others. Nevertheless, when analyzing their modus operandi, the attention has focused on violent and illegal tactics, to the detriment of non-violent and legal tactics. In light of this, and inspired by the literature on hybrid threats, this paper introduces the Coercion-Manipulation-Persuasion framework (CMPf) to holistically analyze the modus operandi of such actors, conceptually labelled as Systems of Non-State Actors (SNSAs). The CMPf is an analytical framework that combines influence modes (i.e., coercion, manipulation, and persuasion) with different categories (i.e., physical/material, symbolic, institutional, and strategic) to hypothesize over the tactics that could be used by SNSAs, thus facilitating analyses and assessments on their activities and providing anticipation and understanding. To exemplify this, three cases are non-exhaustively analyzed through the CMPf: the Nordic Resistance Movement, the Muslim Brotherhood, and Euskadi Ta Askatasuna. This study is a first step towards exploring how studies on terrorism and hybrid threats intersect, and answers the call of the EU Security Union Strategy for mainstreaming hybrid threat considerations into all policy initiatives.